1986
DOI: 10.2136/sssaj1986.03615995005000030039x
|View full text |Cite
|
Sign up to set email alerts
|

Goodness of Fit for Eight Water Infiltration Models

Abstract: Eight infiltration models were investigated for their capability to describe water infiltration into soils. The models were; Philip's, Modified Philip's, Kostiakov's, Talsma and Parlange's, Horton's, and Lewis and Milne's. Field measurements of water infiltration were made using single ring infiltrometers on field plots established on a Norwood soil (Typic Udifluvents) with four long‐term (27 yr) winter cover crop treatments followed by cotton (Gossypium hirsutum L.) each year. The four treatments were; (i) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 0 publications
1
14
0
1
Order By: Relevance
“…The pressure and conductivity were determined as functions of the water content from transient flow data. Measured wetting front depths and the depths predicted from the modified Green-Ampt and Philip models closely agree, as shown inFigure 4 Davidoff and Selim [1986]. performed field infiltration experiments on Norwood fine to silty sandy loam with an initial saturation of about 0.37.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…The pressure and conductivity were determined as functions of the water content from transient flow data. Measured wetting front depths and the depths predicted from the modified Green-Ampt and Philip models closely agree, as shown inFigure 4 Davidoff and Selim [1986]. performed field infiltration experiments on Norwood fine to silty sandy loam with an initial saturation of about 0.37.…”
supporting
confidence: 62%
“…The need for the complete K(h) curve in most solution schemes has limited the ability to validate the models. Attempts at validation typically fit proposed models to cumulative infiltration or wetting front depth measurements by adjusting the parameters rather than using independently measured parameter values [Davidoff and Selim, 1986;Hogarth et al, 1989;Whisler and Bouwer, 1970]. Of the models described the Green-Ampt formulation requires the least parameter characterization, which explains in large part its success: the reduction in measurement…”
Section: I: K(ho)t + Const (8)mentioning
confidence: 99%
“…Infiltration characteristics can mostly be evaluated under either ponded or rainfall conditions or predicted using infiltration models (Haverkamp et al, 1988;Majaliwa and Tenywa, 1998). Several studies have been conducted to quantify the infiltration process (Green and Ampt, 1911;Kostiakov, 1932;Horton, 1940;Philip, 1957a;Talsma and Parlange, 1972;Rao et al, 2006), as well as evaluate infiltration models either for the purpose of validation to establish the model parameters or comparison of model efficiencies and applicability for different soil conditions (Ahmed, 1982;Bach et al, 1986;Davidoff and Salim, 1986;Obiechefu, 1991;Topaloglu, 1999;Wudduvira et al, 2001;Igbadun and Idris, 2007;Egbai et al, 2011) because the models are strongly subjected to soil spatial variability (Dashtaki et al, 2009). Al-Azawi (1985), reported that a lack of knowledge of the model parameters for different soils and locations makes the use of these models difficult.…”
Section: Introductionmentioning
confidence: 99%
“…The value of a, c and m cab be obtained from curve-fittings (Davidoff and Selim 1986). While the above discussed models have been well addressed in the literature (e.g.…”
Section: Introductionmentioning
confidence: 99%